Do Wages and Work Environments Play a Big Role on Employee Performance in Private Organizations? - Lilik Khoiriyah; Harsono (Open Access Indonesia Journal of Social Sciences, 2020)
Human resources are a significant enough part of achieving organizational goals, both large and small companies; a company has modern equipment with high technology. The purpose of understanding and studying human resource management is the knowledge needed to have analytic skills in dealing with management problems, especially in the organization's field. The role of human resources in the company is significant because as the primary driver of all activities or activities of the company in achieving its objectives, both to obtain profits and to maintain the survival of the company. The success or failure of a company in maintaining its existence starts from the human being itself in maintaining the company in maximizing its effectiveness and efficiency. Wages and work environment are factors that significantly affect employee performance. An employee who has high wages or as expected and a pleasant work environment will achieve the company's goals and objectives.